Donor behavior of Sb in ZnO - Liu, H. Y.; Izyumskaya, N.; Avrutin, V.; Ozgur, U.; Yankovich, A. B.; Kvit, A. V.; Voyles, P. M.; Morkoc, H. (My University, 2012)
Electrical behavior of Sb in ZnO:Sb layers doped in a wide concentration range was studied using temperature dependent Hall effect measurements. The layers were grown by plasma-enhanced molecular beam epitaxy, and the Sb concentration was changed by varying the Sb flux, resulting in electron concentrations in the range of 10^16 to nearly 10^20 cm^- 3. Upon annealing, the electron concentration increased slightly and more notable was that the electron mobility significantly improved, reaching a room-temperature value of 110 cm2/V s and a low-temperature value of 145 cm2/V s, close to the maximum of 155 cm2/V s set by ionized impurity scattering. Hall data and structural data suggest that Sb predominantly occupies Zn sublattice positions and acts as a shallow donor in the whole concentration range studied. In the layers with high Sb content ( 1 at. %), acceptor-type compensating defects (possibly Sb on oxygen sites and/or point-defect complexes involving SbO) are formed. The increase of electron concentration with increasing oxygen pressure and the increase in ZnO:Sb lattice parameter at high Sb concentrations suggest that acceptors involving SbO rather than SbZn-2VZn complexes are responsible for the compensation of the donors.
Keywords: doping; ZnO